PENERAPAN FLEET MANAGEMENT SYSTEM UNTUK MENINGKATKAN EFISIENSI BIAYA DAN PRODUKTIVITAS PERUSAHAAN MEKAR JAYA GROUP - Pamungkas, Andhika Ressa; Mandasari, Virginia (Bussman Journal : Indonesian Journal of Business and Management, 2025)
To face business competition and increased cost efficiency and productivity, Mekar Jaya Group implements an efficient and data-driven fleet management strategy. As a consumer good product distribution company, fleet efficiency is very important. The main strategies include preventive maintenance, monitoring driver behavior, route optimization, and the use of telematics-based fleet management systems (FMS). Preventive maintenance helps extend the life of the vehicle and reduce repair costs. Route optimization with GPS and eco-driving education improves fuel efficiency. The Fleet Management System (FMS) allows real-time monitoring to monitor poor driving habits. Qualitative studies through interviews reveal practices such as routine inspections, flexible improvement policies, and the use of technology in operational planning. Demand trend analysis minimizes idle time, while defensive driving training improves safety. This strategy has been proven to reduce Total Cost of Ownership (TCO), increase asset utilization, and maintain profitability without degrading service quality